a) \( \frac{x^{4} y^{-2} \cdot \sqrt{x^{3} y^{5}}}{\sqrt[3]{x^{3} y^{2}} \cdot x^{\frac{5}{3}} \cdot y^{\frac{2}{3}}} \)
Real Tutor Solution
Answer
Solution
Sign in to Unlock Answers for Free!
A Learning Platform Trusted by Millions of Real Students and Teachers.
Reviewed and approved by the UpStudy tutoring team
Mind Expander
Let’s break it down step by step. First, simplify each part of the expression. The top part is \( x^{4} y^{-2} \cdot \sqrt{x^{3} y^{5}} \). Recall that \( \sqrt{x^{3} y^{5}} = x^{\frac{3}{2}} y^{\frac{5}{2}} \). So, we multiply: \[ x^{4} y^{-2} \cdot x^{\frac{3}{2}} y^{\frac{5}{2}} = x^{4 + \frac{3}{2}} y^{-2 + \frac{5}{2}} = x^{\frac{8}{2} + \frac{3}{2}} y^{-\frac{4}{2} + \frac{5}{2}} = x^{\frac{11}{2}} y^{\frac{1}{2}} \] Now, let's simplify the denominator \( \sqrt[3]{x^{3} y^{2}} \cdot x^{\frac{5}{3}} \cdot y^{\frac{2}{3}} \). The cube root gives us \( \sqrt[3]{x^{3}} = x^{1} \) and \( \sqrt[3]{y^{2}} = y^{\frac{2}{3}} \): \[ \sqrt[3]{x^{3} y^{2}} = x^{1} y^{\frac{2}{3}} \Rightarrow x^{1} y^{\frac{2}{3}} \cdot x^{\frac{5}{3}} \cdot y^{\frac{2}{3}} = x^{1 + \frac{5}{3}} y^{\frac{2}{3} + \frac{2}{3}} = x^{\frac{3}{3} + \frac{5}{3}} y^{\frac{4}{3}} = x^{\frac{8}{3}} y^{\frac{4}{3}} \] Now, putting it all together, we have: \[ \frac{x^{\frac{11}{2}} y^{\frac{1}{2}}}{x^{\frac{8}{3}} y^{\frac{4}{3}}} = x^{\frac{11}{2} - \frac{8}{3}} y^{\frac{1}{2} - \frac{4}{3}} \] To simplify \( \frac{11}{2} - \frac{8}{3} \) and \( \frac{1}{2} - \frac{4}{3} \), we need a common denominator. 1. For \( \frac{11}{2} - \frac{8}{3} \): - Common Denominator: 6 - \( \frac{11}{2} = \frac{33}{6}, \frac{8}{3} = \frac{16}{6} \rightarrow \frac{33}{6} - \frac{16}{6} = \frac{17}{6} \) 2. For \( \frac{1}{2} - \frac{4}{3} \): - Common Denominator: 6 - \( \frac{1}{2} = \frac{3}{6}, \frac{4}{3} = \frac{8}{6} \rightarrow \frac{3}{6} - \frac{8}{6} = -\frac{5}{6} \) Thus, we have: \[ = x^{\frac{17}{6}} y^{-\frac{5}{6}} = \frac{x^{\frac{17}{6}}}{y^{\frac{5}{6}}} \] The final simplified expression is: \[ \frac{x^{\frac{17}{6}}}{y^{\frac{5}{6}}} \]